Institutional changes of SPACs - Milan Lakicevic; Yochanan Shachmurove; Milos Vulanovic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We document the changes of corporate design of modern Specified Purpose Acquisition Companies (SPACs) from 2003 to 2012. We assign the impact on changes of SPACs to each of the three groups of stakeholders: founders, investors and underwriters and test whether institutional characteristics of SPACs determine the success of their merger outcomes. We document that SPACs significantly redesigned its structure in the period under observation. Additionally, the probability of the merger for SPACs is increasing if they are able to; announce the deal soon after the IPO, focus that deal on China and have their IPO underwritten by EarlyBirdCapital
Keywords: 330; spac; Blank Checks; SPACs; Blank Checks